2014
DOI: 10.5539/ies.v8n1p113
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Early Reading Skills: Examining the Print Features of Preschool Children’s Book

Abstract: The purpose of this study is to examine the uses of print features in preschool children's books in the US and Turkey, in order to helping adults to understand print features and supporting children's print awareness. In this context, two hundred children's books was randomly selected from the US and Turkey. Document analysis was used for examining the children's books. For the analysis of how to use print features, this study used coding systems adapted from McCarier, Pinnel, and Fountas (2000) and Zucker, Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…It has been suggested that books that contain a good deal of such print are an important vehicle for early literacy learning because they support the development of print awareness (Cetin & Bay, 2015; Zucker, Justice, & Piasta, 2009). This idea is based on the finding that preschool children pay more attention to writing that is large or bold or embedded in pictures than writing that does not have these characteristics (Neumann, Acosta, & Neumann, 2014; Neumann, Summerfield, & Neumann, 2015; Smolkin, Conlon, & Yaden, 1988; Smolkin, Yaden, Brown, & Hofius, 1992).…”
Section: Characteristics Of Print In Books For Preschool Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that books that contain a good deal of such print are an important vehicle for early literacy learning because they support the development of print awareness (Cetin & Bay, 2015; Zucker, Justice, & Piasta, 2009). This idea is based on the finding that preschool children pay more attention to writing that is large or bold or embedded in pictures than writing that does not have these characteristics (Neumann, Acosta, & Neumann, 2014; Neumann, Summerfield, & Neumann, 2015; Smolkin, Conlon, & Yaden, 1988; Smolkin, Yaden, Brown, & Hofius, 1992).…”
Section: Characteristics Of Print In Books For Preschool Childrenmentioning
confidence: 99%
“…In the only other study, to our knowledge, to have examined these issues, Cetin and Bay (2015) examined the print in 100 books designed for US preschoolers. They found that most of the books contained several instances of visually salient print.…”
Section: Characteristics Of Print In Books For Preschool Childrenmentioning
confidence: 99%
See 3 more Smart Citations